Detection, Occurrence and Fate of Emerging Contaminants in Agricultural Environments. (1st October 2018) - Snow, Daniel D.; Cassada, David A.; Biswas, Saptashati; Shafieifini, Mohammedreza; Li, Xu; D'Alessio, Matteo; Carter, Laura; Sallach, J. Brett
Abstract : A total of 75 papers published in 2017 were reviewed ranging from detailed descriptions of analytical methods, to fate and occurrence studies, to ecological effects and sampling techniques for a wide variety of emerging contaminants likely to occur in agricultural environments. New methods and studies on veterinary pharmaceuticals, steroids, antibiotic resistance genes, and engineered nanoparticles agricultural environments continue to expand our knowledge base on the occurrence and potential impacts of these compounds. This review is divided into the following sections: Introduction, Analytical Methods, Fate and Occurrence, Pharmaceutical Metabolites, Anthelmintics, Antibiotic Resistence Genes, and Engineered Nanomaterials.